Effects of source doping profile on device characteristics of lateral and vertical tunnel field-effect transistors - Vinh, Luu The; Chien, Nguyen Dang (Vietnam Journal of Science and Technology, 2015)
The source doping engineering, the low bandgap material and the vertical tunneling structure have recently been considered as most effective techniques to resolve the on-current issue in tunnel field-effect transistors (TFETs). In this paper, the effects of source doping profile, including the concentration and gradient, on the device characteristics are adequately elucidated in lateral and vertical TFETs using low bandgap germanium to allow a comprehensive comparison between the two major TFET architectures for the first time. Similar dependences of the on-current on the source concentration are observed in lateral and vertical TFETs, except that the on-current of vertical TFETs is always greater than that of lateral TFETs approximately one order of magnitude. With different contributions of the lateral and vertical tunneling components in the subthreshold region, the subthreshold swing of vertical TFETs first decreases at small concentrations, then increases at medium values, and finally decreases again at high concentrations, whereas that of lateral counterparts always decreases exponentially with increase in the source concentration. The on-current of lateral TFETs is significantly decreased, while that of vertical TFETs is almost invariable with increasing the source doping gradient. With competitive advantages of the vertical TFET architecture in on-current, subthreshold swing and device fabrication, vertical TFETs using low bandgap semiconductors are promising for use in low power applications.